2006
DOI: 10.1007/s10439-006-9123-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approach to Estimating the Effects of Blood Properties on Changes in Intra-stent Flow

Abstract: In this study various blood rheological assumptions are numerically investigated for the hemodynamic properties of intra-stent flow. Non-newtonian blood properties have never been implemented in blood coronary stented flow investigation, although its effects appear essential for a correct estimation and distribution of wall shear stress (WSS) exerted by the fluid on the internal vessel surface. Our numerical model is based on a full 3D stent mesh. Rigid wall and stationary inflow conditions are applied. Newton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 48 publications
2
35
0
1
Order By: Relevance
“…Rajamohan et al 22 studied pulsatile and non-Newtonian blood flow through a stent with a helical strut matrix and identified recirculation zones immediately upstream and downstream of each strut intersection. Similar other studies 3,10,12,24 have shown that stents, depending on their design, cause significant alterations in hemodynamics leading to particular zones which could be susceptible to smooth cell proliferation and restenosis. Balossino et al 2 modeled expansion of four different stents against plaque and artery using finite element analysis (FEA) and used the expanded geometries to evaluate the hemodynamics.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Rajamohan et al 22 studied pulsatile and non-Newtonian blood flow through a stent with a helical strut matrix and identified recirculation zones immediately upstream and downstream of each strut intersection. Similar other studies 3,10,12,24 have shown that stents, depending on their design, cause significant alterations in hemodynamics leading to particular zones which could be susceptible to smooth cell proliferation and restenosis. Balossino et al 2 modeled expansion of four different stents against plaque and artery using finite element analysis (FEA) and used the expanded geometries to evaluate the hemodynamics.…”
Section: Introductionsupporting
confidence: 77%
“…(3) and (4), respectively. It should be noted that the wall area over which the surface integrals for p l (t) and p r (t) are calculated includes only the area exposed to flow, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, g and q were chosen equal to 4 9 10 -3 Pa.s and 1.05 9 10 3 kg/m 3 respectively, being standard values used in literature (e.g. [1,2,34]). …”
Section: Bvf Estimationmentioning
confidence: 99%
“…36 Time-dependent simulations were also performed for the 2 stent cases described here by using the standard Ku waveform, which has a Womersley number of 6.5 and does not exhibit regions of reversed flow. 37 However, the key hemodynamic features described in this article for this waveform applied to our model (a straight tube) tended to vary principally only in amplitude over the pulsatile cycle, as observed in the simulations of Benard et al 16 and Seo et al 14 Thus, we have used steady flow simulations in the present work. Time-dependent and transient effects can be significant under certain conditions and are the focus of further research.…”
Section: Caveatsmentioning
confidence: 89%
“…11 Recent computational hemodynamic (CHD) studies on the effects of stents on arterial hemodynamics have generally used idealized mathematic modeling of the artery and superimposed stent. [12][13][14][15][16][17] These simulations have provided some useful information about the local WSS behavior near the struts and cell centers as a function of strut dimensions, stent porosity, and flow rates. Although more detailed analysis of flow over stent struts has been undertaken by using 2D models, 18 which have also been used to predict deposition rates for drug-eluting stents, 19 the importance of 3D hemodynamic behavior near the struts and wall has recently been recognized.…”
mentioning
confidence: 99%